PERANCANGAN DAN PEMBANGUNAN SISTEM VOICE OVER INTERNET PROTOCOL - Laurenz, Laurenz; Putro, Endi (Teknik dan Ilmu Komputer, 2012)
Rapid development in communication encourage community interest in switching to a low-cost communications technology by relying on the internet known as VoIP (Voice over Internet Protocol). VoIP is a technology that enables voice communications using IP (Internet Protocol) to run over packet networks. This technology works by changing the way certain sounds into a digital format that can be transmitted over an IP network. The results of this experiment is able to communicate from computer to computer, computer to PSTN, PSTN to the computer, and users can call from computer to PSTN number from anywhere without long distance charges.Â Keywords: VoIP, internet protocol, PSTN, server, client.